Digitalization’s Role in Strengthening Empowerment and Product Innovation Effects on Business Sustainability: Evidence From Rumah Bumn Jambi - Rina Mardiana; Rike Setiawati; Besse Wediawati (Universitas Darwan Ali, 2025)
Business sustainability has become a strategic challenge for entrepreneurs in facing dynamic and increasingly competitive market conditions. This study aims to analyze the role of empowerment and product innovation in supporting business sustainability, with digitalization positioned as a moderating variable. The research focuses on Rumah BUMN Jambi, which actively contributes to enterprise development by providing training, mentoring, and facilitating access to markets and digital technologies. A quantitative approach was employed using Structural Equation Modeling (SEM) as the analytical method. Data were collected through surveys of entrepreneurs fostered by Rumah BUMN Jambi. The findings reveal that empowerment has a positive effect on business sustainability, and product innovation also contributes significantly to enhancing sustainability. However, digitalization was found to negatively moderate these relationships, indicating that at certain levels, the application of digital technologies may weaken the positive influence of empowerment and product innovation on business sustainability. These results provide important implications for designing empowerment and innovation strategies that are more adaptive to digital advancements, thereby strengthening resilience and ensuring long-term sustainability.